Child-Focused Mental Health Interventions for Disasters Recovery: A Rapid Review of Experiences to Inform Return-to-School Strategies After COVID-19 - Gómez, Gabriela; Basagoitia, Armando; Burrone, María Soledad; Rivas, Marlene; Solís-Soto, María Teresa; Dy Juanco, Sean; Alley, Hugh (Frontiers in Psychiatry, 2021)
Mental health interventions to address the mental health needs during early childhood (age <12), returning to school in the post-COVID-19 environment are essential worldwide. Currently, basic characteristics of child-focused, post-crisis interventions are unknown but essential to developing high-quality, expedient RTC programs. We conducted a rapid systematic review, via established PICO methodology, to appraise the characteristics of such interventions. We queried databases (PubMed, PsycInfo, ERIC) for English and Spanish publications describing mental health interventions to reduce mental health symptoms and sequelae among children exposed to disasters and other community crisis. We described interventions characteristics including, type of intervention, length, session number, staff delivering the intervention number and characteristics. A total of 18 original articles meets inclusion criteria, 11 correspond to a controlled trial type of study and 15 addressed PTSD after disaster or crisis situations. Cognitive Behavioral Therapy (CBT) was the most common intervention type, and School-based/related interventions were the most common method and 5 articles described an important role of teachers as mediators of therapies.